1723. Mumps Attack Rates Following Administration of a Third Dose of MMR Vaccine to School-Aged Children, Arkansas, 2016–2017. (26th November 2018) - Guo, Angela; Ayers, Tracy; Leung, Jessica; Fields, Virgie; Va, Puthiery; Safi, Haytham; Waters, Catherine; Wheeler, J Gary; Marin, Mona; Patel, Manisha; Routh, Janell; Haselow, Dirk
Abstract: Background: During the 2016–2017 school year, the largest mumps outbreak in the United States since 2006 occurred in Arkansas with nearly 3, 000 cases. As part of outbreak response, a third dose of measles–mumps–rubella vaccine (MMR3) was offered at 27 schools with mumps attack rates ≥5 cases/1, 000 students. We compared attack rates after vaccination clinics among students who received MMR3 and students with 2 MMR vaccine doses. Methods: We obtained information on school enrollment and student immunization status from school registries, and mumps case status from Arkansas's National Electronic Disease Surveillance System database. We included students aged 6–21 years who had previously received ≥2 doses of MMR vaccine. We used Arkansas's Immunization Information System to identify students who received MMR3. We included schools with at least 1 mumps case after their vaccination clinic. We calculated mumps attack rates by 2- and 3-dose MMR vaccine recipients. Observation time started 14 days after each clinic to allow for development of an immune response to MMR3, and continued to the end of the 2016–2017 school year. Observation time varied by school as schools held clinics on different dates. Results: A total of 18 schools (10 elementary, 8 middle/junior high) with 10, 275 students who had previously received ≥2 doses of MMR (85% of total enrolled) met inclusion criteria. Median number of students per school was 553. Median student age was 11 years (range, 6–18) and 1, 525 students received MMR3. MMR3 uptake varied by school (median, 12%; range, 2–33%; interquartile range, 7–22%). A total of 12 mumps cases occurred among MMR3 recipients and 122 cases among 2-dose recipients. School-specific attack rates ranged from 0 to 23 cases/1, 000 students among 3-dose recipients, and 2–41 cases/1, 000 students among 2-dose recipients. Mumps attack rates within each school were lower for 3-dose recipients vs. 2-dose recipients in all but one school ( P < .05). The differences in attack rates between 2- and 2-dose recipients ranged from −5 to 23 cases/1, 000 students (median, 5/1, 000). Conclusion: Mumps attack rates were lower in 3-dose vs. 2-dose MMR vaccine recipients after MMR3 vaccination clinics, supporting a benefit of MMR3 for persons in outbreak settings. Further analysis is needed to determine impact of MMR3 on duration and size of mumps outbreaks. Disclosures: All authors: No reported disclosures.